Breaking voice identity perception: Expressive voices are more confusable for listeners. Issue 9 (September 2019) - Lavan, Nadine; Burston, Luke FK; Ladwa, Paayal; Merriman, Siobhan E; Knight, Sarah; McGettigan, Carolyn
The human voice is a highly flexible instrument for self-expression, yet voice identity perception is largely studied using controlled speech recordings. Using two voice-sorting tasks with naturally varying stimuli, we compared the performance of listeners who were familiar and unfamiliar with the TV show Breaking Bad . Listeners organised audio clips of speech with (1) low-expressiveness and (2) high-expressiveness into perceived identities. We predicted that increased expressiveness (e.g., shouting, strained voice) would significantly impair performance. Overall, while unfamiliar listeners were less able to generalise identity across exemplars, the two groups performed equivalently well when telling voices apart when dealing with low-expressiveness stimuli. However, high vocal expressiveness significantly impaired telling apart in both the groups: this led to increased misidentifications, where sounds from one character were assigned to the other. These misidentifications were highly consistent for familiar listeners but less consistent for unfamiliar listeners. Our data suggest that vocal flexibility has powerful effects on identity perception, where changes in the acoustic properties of vocal signals introduced by expressiveness lead to effects apparent in familiar and unfamiliar listeners alike. At the same time, expressiveness appears to have affected other aspects of voice identity processing selectively in one listener group but not the other, thus revealing complex interactions of stimulus properties and listener characteristics (i.e., familiarity) in identity processing.